2012
DOI: 10.1155/2012/175408
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PAFR as Part of a Prosurvival Response to Chemotherapy: A Novel Target for Combination Therapy in Melanoma

Abstract: Melanoma cells express the platelet-activating factor receptor (PAFR) and, thus, respond to PAF, a bioactive lipid produced by both tumour cells and those in the tumour microenvironment such as macrophages. Here, we show that treatment of a human melanoma SKmel37 cell line with cisplatin led to increased expression of PAFR and its accumulation. In the presence of exogenous PAF, melanoma cells were significantly more resistant to cisplatin-induced cell death. Inhibition of PAFR-dependent signalling pathways by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 23 publications
3
42
0
4
Order By: Relevance
“…These data are of great interest since the dose of EVOOE used for this experiment was non-toxic per se to the cells themselves, and this indicates a synergic effect in combination with paclitaxel. It can be hypothesized that the cytotoxicity enhancement of paclitaxel could be attributed to the alteration in gene expression occurring at low doses of phenolic extract, as observed in our previous study (20), that chemosensitize the cells by altering pathways involved in cell growth and proliferation such as platelet-activating factor (PAF) receptor signaling or PI3K signaling (37,41,42). …”
Section: Discussionmentioning
confidence: 75%
“…These data are of great interest since the dose of EVOOE used for this experiment was non-toxic per se to the cells themselves, and this indicates a synergic effect in combination with paclitaxel. It can be hypothesized that the cytotoxicity enhancement of paclitaxel could be attributed to the alteration in gene expression occurring at low doses of phenolic extract, as observed in our previous study (20), that chemosensitize the cells by altering pathways involved in cell growth and proliferation such as platelet-activating factor (PAF) receptor signaling or PI3K signaling (37,41,42). …”
Section: Discussionmentioning
confidence: 75%
“…iNOS and the production of PGE 2 and NO in RAW264.7 cells. COX-2 and iNOS are both critical enzymes associated with macrophage-mediated development and progression of inflammation (19)(20)(21); therefore, effects of PLE on the mRNA level of COX-2 and iNOS were analyzed and quantified in LPS-stimulated RAW264.7 cells. RT-PCR analysis showed that LPS treatment alone enhances the expression of COX-2 and iNOS, and this increase was reverted by pretreatment with PLE in a dose-dependent manner (Fig.…”
Section: Ple Inhibits Lps-induced Mrna Expression Of Cox-2 Andmentioning
confidence: 99%
“…The contribution of PAFRdependent signalling in tumour repopulation was also demonstrated in its response to chemo therapy and radiotherapy. PAF protects tumour cells from druginduced cell death, and the admin istration of PAFR antagonists blocks its protective effect [11][12][13] . Radiation therapy is among the most potent inducers of PAFR ligands through the oxidation of phospholipids 14 , whose forma tion is independent of LPCAT.…”
mentioning
confidence: 99%